Crafting the Next Generation of CGIAR Gender Research - Pyburn, Rhiannon; Monterroso, Iliana; Malapit, Hazel; Kosec, Katrina; Meinzen-Dick, Ruth S.; Twyman, Jennifer; Najjar, Dina (2019)
Rhiannon Pyburn, Illiana Monterroso, Hazel Malapit, Katrina Kosec, Ruth Meinzen-Dick, Jennifer Twyman, and Dina Najjar POLICY SEMINAR Crafting the Next Generation of CGIAR Gender Research Co-Organized by the CGIAR Research Program on Policies, Institutions, and Markets and IFPRI OCT 30, 2019 - 12:15 PM TO 01:45 PM EDT